2014
DOI: 10.1016/j.cryobiol.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of hepatocyte (HepG2) cell monolayers: Impact of trehalose

Abstract: 23A simple method to cryogenically preserve hepatocyte monolayers is currently not available but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…increased recovery of viable cells to 35% (Fig 1). This finding is similar to our previous results 336 found with HepG2 monolayers [47].…”
supporting
confidence: 94%
“…increased recovery of viable cells to 35% (Fig 1). This finding is similar to our previous results 336 found with HepG2 monolayers [47].…”
supporting
confidence: 94%
“…Trehalose, a macromolecular substance, greatly affects cells osmotic pressure. Trehalose on cryopreservation could protect the cell and tissue activity (Lee et al, ; Stokich et al, ; Zhang, Hu, et al, ). Previous studies suggest that trehalose, in a dose‐dependent manner has different effects on cryopreservation of bovine semen (Hu et al, ), boar testes (Lee et al, ) and bovine calf testes (Zhang, Wang, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose improves mammalian cells’ ability to withstand cold temperature (Eroglu et al, ). Incubation with trehalose is beneficial for long‐term preservation of cells (Stokich et al, ). Trehalose is also applied as an antioxidant in frozen–thawed bovine calf testicular tissue (Zhang, Hu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Growth of cells in medium supplemented with trehalose allowing trehalose uptake via fluid‐phase endocytosis prior to freezing has been shown to increase cryosurvival . The mechanisms have been attributed to metabolic downregulation by trehalose or osmotic stress caused by culturing with trehalose activating signaling pathways that allow cells to better cope with cryopreservation stress.…”
Section: Discussionmentioning
confidence: 99%
“…30 Fluid-phase endocytosis, which is an inherent property of cells to incorporate membrane-impermeable molecules, can also be used to introduce trehalose into cells. 31 It has been shown that growth of cells in the presence of trehalose, allowing uptake through endocytosis, increases cell stability during cryopreservation [32][33][34] and freeze-drying. 31 Trehalose uptake via fluid-phase endocytosis shows a linear dependency with respect to the extracellular concentration and incubation time and is inhibited at low temperatures.…”
Section: Introductionmentioning
confidence: 99%